What Is the Role of Pharmacists in Treating COVID-19 Patients? The Experiences and Expectations of Front Line Medical Staff - Xuedong Jia; Wan Zhang; Shuzhang Du; Linlin Wen; Hongye Li; Zhao Yin; Jun Li; Xiaojian Zhang (Frontiers Media S.A., 2021)
Aims: The study aimed to understand the role and the core values of pharmacists and the professional expectations of medical staff for pharmacists in treating COVID-19 patients from the perspectives of the frontline medical staff. The findings help to understand and provide a reference for the career growth path of future pharmacists.Methods: A phenomenological method was used to conduct in-depth interviews with frontline medical staff working in isolation wards during COVID-19. The interview data were analyzed, and the themes were extracted.Results: Pharmacists played a positive role in ensuring the supply of non-routinely stocked drugs, including traditional Chinese medicine preventative preparations, providing drug information and medication consultation for complex patients, and identifying adverse drug reactions. However, at present, the integration of pharmacists and nurses is poor with inadequate communication, and the pharmaceutical care activities provided to physicians were still not comprehensive.Conclusions: The level of pharmaceutical care provided by pharmacists needs to be further strengthened. Frontline medical teams generally have high professional expectations for pharmacists, including expecting pharmacists to become drug therapy experts. They expect pharmacists to fully participate in clinical decision-making, especially playing a central role in managing drug interactions, contraindications, and other clinical uses of drugs.